Policy options for a socially balanced climate policy - Gregor Schwerhoff; Nguyen Thang Dao; Ottmar Edenhofer; Gianluca Grimalda; Michael Jakob; David Klenert; Jan Siegmeier (Kiel Institute for the World Economy (IfW), 2017)
Climate policies, including removing fossil fuel subsidies or imposing carbon prices, can be designed in a way that is both efficient in addressing climate change and results in a fair distribution of the associated costs.
Keywords: D62; E62; H21; H22; 330; G20; climate policy; distribution